Community Empowerment Strategy In Developing Agrotourism Village In Kuningan Regency, West Java - Rd. Ahmad Buchari; Sulaiman Zuhdi; Azlan Abas; Kadaruddin Aiyub; Entang Adhy Muhtar; Ahmad Zaini Miftah; Riki Satia Muharam; Darto Darto (Journal of Government and Civil Society, 2024)
The enhancement of local resources through agrotourism presents significant opportunities for economic growth, social benefits, and environmental sustainability in rural communities. This study explores strategic approaches to community empowerment in the development of agrotourism villages within Kuningan Regency, West Java, an area rich in agricultural potential. A qualitative case study method was adopted, gathering data through observations, in-depth interviews, and focus group discussions (FGD). The findings underscore that agrotourism village development requires an integrated approach, focusing on robust governance, active community participation, innovation, and cross-sector collaboration to efficiently manage and promote tourism destinations. The study highlights the critical role of government policy and budgetary support in establishing programs that leverage local agricultural strengths, empowering communities to participate actively in sustainable tourism. By employing a comprehensive, long-term development model, agrotourism can be effectively harnessed to yield both economic and social value for local communities, while also prioritizing environmental conservation. This research provides valuable insights into how structured community empowerment and strategic collaboration can unlock the full potential of agrotourism as a sustainable development pathway for rural regions.Peningkatan sumber daya lokal melalui agrowisata menghadirkan peluang signifikan untuk pertumbuhan ekonomi, manfaat sosial, dan keberlanjutan lingkungan di komunitas pedesaan. Studi ini mengeksplorasi pendekatan strategis dalam pemberdayaan masyarakat untuk pengembangan desa agrowisata di Kabupaten Kuningan, Jawa Barat, yang kaya akan potensi pertanian. Metode studi kasus kualitatif diterapkan, dengan pengumpulan data melalui observasi, wawancara mendalam, dan diskusi kelompok terarah (FGD). Hasil penelitian menekankan bahwa pengembangan desa agrowisata membutuhkan pendekatan terintegrasi yang berfokus pada tata kelola yang kuat, partisipasi aktif masyarakat, inovasi, serta kolaborasi lintas sektor untuk mengelola dan mempromosikan destinasi wisata secara efisien. Studi ini menyoroti peran penting dukungan kebijakan dan anggaran pemerintah dalam membentuk program-program yang memanfaatkan kekuatan pertanian lokal, memberdayakan masyarakat untuk berpartisipasi aktif dalam pariwisata berkelanjutan. Dengan menerapkan model pengembangan yang menyeluruh dan jangka panjang, potensi agrowisata dapat dimanfaatkan secara efektif untuk memberikan nilai ekonomi dan sosial bagi masyarakat lokal, sambil tetap memprioritaskan pelestarian lingkungan. Penelitian ini memberikan wawasan berharga tentang bagaimana pemberdayaan masyarakat yang terstruktur dan kolaborasi strategis dapat membuka potensi penuh agrowisata sebagai jalur pembangunan berkelanjutan bagi wilayah pedesaan.